Effects of Information Communication Technology and Customer Service on Customers’ Satisfaction: A Study of the Courier and Parcel Industry in Nigeria - Thomas Sule, Asipita (British Journal of Marketing Studies, 2024)
The study investigates the effects of information communication technology and customer service on customers’ satisfaction in the courier and parcel industry in Nigeria. Correlation design was used to investigate the relationship between the independent variables ICT and customer service and the dependent variable customer satisfaction. Questionnaire was administered conveniently to sample 220 customers of the courier and parcel industry in Nigeria, and data analysis carried out using SPSS version 21. The study revealed a significant relationship between ICT and customer satisfaction in the courier and parcel industry in Nigeria. Also, the study found a positive relationship between customer service and customer satisfaction in the courier and parcel industry of Nigeria. Practical implication for service managers and direction for future studies are presented.